1988
DOI: 10.22260/isarc1988/0072
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to the Development of Construction Site Crane Operations

Abstract: The following is a review of the current status and future plans of the research concerning tower crane operations, carried out by the Technical Research Centre of Finland (VTT). Firstly, an empirical time-motion study of crane operations on building sites is described. The results can be used for creating a crane selection guideline in a textual or knowledge based form and in crane automation ideas evaluation. Secondly, the current crane automation research results carried out by VTT are summarized and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Toward the end of 1980s, a comprehensive study on construction robotics showed that the automation of the crane should allow the improvement of the most frequent construction site operations (Elsila et al, 1988). At the time, concrete pouring was a frequent crane operation that can amount to up to 40% of all crane operations onsite, as in the example used in the present work.…”
Section: Project Progress Using Tower Crane's Datamentioning
confidence: 87%
See 1 more Smart Citation
“…Toward the end of 1980s, a comprehensive study on construction robotics showed that the automation of the crane should allow the improvement of the most frequent construction site operations (Elsila et al, 1988). At the time, concrete pouring was a frequent crane operation that can amount to up to 40% of all crane operations onsite, as in the example used in the present work.…”
Section: Project Progress Using Tower Crane's Datamentioning
confidence: 87%
“…Toward the end of 1980s, a comprehensive study on construction robotics showed that the automation of the crane should allow the improvement of the most frequent construction site operations (Elsila et al. , 1988).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The basic breakdown into four segments (i.e. without addressing the blind part of the cycle) differs also from the common breakdown into two segments only, loading/unloading and travel used by other researchers (Elsilä et al, 1988;Price and Harris, 1992;Leung and Tam, 1999). (Note that although the "start blind lift" time appears in Figure 1 to the right of the "start travel" time, the latter does not necessarily precede the former; this issue is addressed later in the "Integration and Validation" section.)…”
Section: Site Analysis -Tower Cranes Blind Liftsmentioning
confidence: 94%
“…It also assessed the prerequisites for automation (for a wider treatment of these, see [1]), the need for development of methods and technology as well as the profitability of automation applications. Emphasis was given to three stages that are central to the automation of the crane's working cycle: automation of gripping and releasing, automation of motion control and automation of load positioning.…”
Section: Crane Automationmentioning
confidence: 99%